2018
DOI: 10.1039/c8em00264a
|View full text |Cite
|
Sign up to set email alerts
|

Differences in bulk and microscale yttrium speciation in coal combustion fly ash

Abstract: Yttrium speciation in coal fly ash differs depending on the scale of the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 56 publications
0
35
1
Order By: Relevance
“…This characteristic along with the low concentration and dispersed nature of REEs have caused difficulties in characterizing the modes of occurrence of REEs in fly ash using traditional approaches. However, many recent studies have addressed this challenge using advanced characterization tools, such as X-ray Absorption Near Edge Structure (XANES), micro-X-Ray Absorption Near Edge Structure (µ-XANES), laser ablation inductively coupled plasma mass spectroscopy (LA-ICP-MS), multimodal image analysis, and sensitive high resolution ion microprobe-reverse geometry SHRIMP-RG [65][66][67][68][69][70]. In addition, systematic SEM-EDX, TEM-EDX, and sequential chemical extraction (SCE) studies have been performed on coal combustion ashes, which also provided valuable information regarding the REE occurrence modes and potential processing routes [71][72][73][74][75][76][77][78].…”
Section: Modes Of Occurrence Of Rees In Coal Combustion Ashmentioning
confidence: 99%
“…This characteristic along with the low concentration and dispersed nature of REEs have caused difficulties in characterizing the modes of occurrence of REEs in fly ash using traditional approaches. However, many recent studies have addressed this challenge using advanced characterization tools, such as X-ray Absorption Near Edge Structure (XANES), micro-X-Ray Absorption Near Edge Structure (µ-XANES), laser ablation inductively coupled plasma mass spectroscopy (LA-ICP-MS), multimodal image analysis, and sensitive high resolution ion microprobe-reverse geometry SHRIMP-RG [65][66][67][68][69][70]. In addition, systematic SEM-EDX, TEM-EDX, and sequential chemical extraction (SCE) studies have been performed on coal combustion ashes, which also provided valuable information regarding the REE occurrence modes and potential processing routes [71][72][73][74][75][76][77][78].…”
Section: Modes Of Occurrence Of Rees In Coal Combustion Ashmentioning
confidence: 99%
“…The TEM approach employed here improved the spatial resolution of other analyses, such as the bulk ICP-MS chemical analysis and the XAS approach applied by Taggart et al [36], and subsequently revealed substantial heterogeneity of REE forms within an individual fly ash grain. Unlike the indications of minerals seen in other studies [12,13], as in the work by Hood et al [18], the mineralogy of the particles is elusive.…”
Section: Discussionmentioning
confidence: 81%
“…Nevertheless, the EDS scan of the mineral showed the presence of Ce and Nd (Figure 7). This fly ash sample was also examined by Taggart et al [36] (denoted as "App-FA3" in that study) for Y modes of occurrence through microprobe X-ray Absorption Spectroscopy (XAS) techniques. That study also reported distinct Y species (e.g., Y distributed in glasses, YPO 4 particles), suggesting that REE occur in widely variable forms in this fly ash.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations